Perancangan Sistem Informasi Penggajian Berbasis Website (Studi Kasus : CV. Andafcorp Bekasi) - Fachrur Rozi; Rinna Rachmatika (CV. Multi Kreasi Media, 2022)
CV. Andafcorp is a company in the field of digital marketing agency that understands business needs in the internet marketing field by experienced and Google-certified practitioners to increase business in the internet field and achieve increased profits. The payroll data processing process at the current company uses a simple program, namely MS. Excel. So that data processing will be more complicated if the process is still using a simple auxiliary program as a tool, because in inputting data and compiling reports, accuracy and precision are needed, because the incoming data can increase and or change at any time. The thing from this design is a computerized web-based employee payroll information system. Making it easier for digital data processing, both in data input and in making reports in order to advance a service to company employees.